Assessment of end-of-life electric vehicle batteries in China: Future scenarios and economic benefits. (November 2021) - Jiang, Songyan; Zhang, Ling; Hua, Hui; Liu, Xuewei; Wu, Huijun; Yuan, Zengwei
Graphical abstract: Highlights: Traction batteries wastes are estimated to be 1.5–3.3 million tons by 2040 in China. Battery recycling for energy storage shows more economic attraction. National coordination for the rational layout of recycling system is necessary. Abstract: A better understanding of the waste of end-of-life batteries from electric vehicles (EVs) is a basis for their sustainable management. This study aims to estimate the waste of end-of-life EV batteries during 2006–2040 in China and to analyze the opportunities and challenges of subsequent utilization, based on a developed numerical model, real market data, and elaborately developed scenarios. The result shows that end-of-life batteries would increase from 0.1 to 7.8 thousand tons during 2012–2018, and then to 1500–3300 thousand tons in 2040. Of the waste streams, around 50% are estimated to be metal materials, representing great opportunities for battery recycling for material recovery. Economically, battery recycling for energy storage is estimated to create more economic benefits compared with that for material recovery solely (147.8 versus 76.9 billion US dollars). However, the supply of end-of-life batteries can hardly meet the demand for renewable energy storage in the near future, and a spatial mismatch of the supply and demand of energy storage capacity exists between the eastern and western regions in China. Accordingly, this study highlights national coordination for the rational layout of the collection, disassembly, and remanufacture facilities for the second use of end-of-life EV batteries in China.